Terbukti E-Leadership Competencies Memiliki Pengaruh Terbesar Dibanding Transformational Leadership, Dan Coaching Leadership Terhadap Employee Wellbeing - Ismadya Putra, Erlangga; Tiarapuspa, Tiarapuspa (Jurnal Etnik: Ekonomi-Teknik, 2023)
The aim of this research is to analyze the effect of Transformational Leadership, E-leadership Competencies, and Coaching Leadership on Employee Wellbeing among employees of PT. Rita Retailindo in Cilacap. The data collection technique used in this study is non-probability sampling. In taking the sample, the researcher will use a non-probability sampling method called purposive sampling technique with a total of one hundred and forty-eight employees collected in the managerial division of PT. Rita Retailindo in Cilacap. The hypothesis testing used in this study was using AMOS software version 24. The results of testing the hypothesis in this study indicate that there is a positive effect of Transformational Leadership, E-Leadership Competence, Coaching Leadership, on Employee Wellbeing